Pengaruh GPM, NPM, ROA, ROE, dan Kebijakan Kepimpinan tehadap Pertumbuhan Laba dengan GCG sebagai Moderasi: (Studi pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Silvi Dwi Anggraini; Hari Setiono; Nurdiana Fitri Isnaini (Universitas 17 Agustus 1945 Semarang, 2024)
The aim of this research is to explain the effect of GPM, NPM, ROA, ROE, and Leadership Policy on Profit Growth with GCG as a Moderating Variable. This type of research is quantitative, where data is processed using the SPSS application. The sample in the study consists of 10 companies from a total population of 15. The sample was determined using Purposive Sampling, which selects samples based on specific criteria. The data analysis techniques used include descriptive statistics, classical assumption tests (normality test, linearity test, multicollinearity test, autocorrelation test, and heteroscedasticity test), multiple linear regression analysis, hypothesis testing (t-test and F-test), moderated regression analysis, and the coefficient of determination. The data used are secondary data in the form of annual financial reports available on the Indonesia Stock Exchange (IDX). The results of this study show that GPM, NPM, ROE, and Leadership Policy have a significant effect on profit growth, while ROA does not have a significant effect on profit growth. For the moderating variable, GCG moderates the relationship between NPM, ROA, and Leadership Policy on profit growth, but GCG does not moderate the relationship between GPM and ROA on profit growth.